Che genere di diritto? Il controverso rapporto tra movimenti delle donne e trasformazioni dell’ordinamento giuridico - La Rocca, Delia (SocietàMutamentoPolitica, 2021)
Women movement have long seemed little interested in law, and traditional legal scholars were little interested in gender studies. However, throughout the twentieth century, women’s movements produced a real revolution in the legal order. This paper discusses the different stages of the relationship between women’s movements and the Italian way to gender equal opportunities.